2019
DOI: 10.1158/1055-9965.epi-18-0825
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Access to a Regular Primary Care Physician in Mediating Immigration-Based Disparities in Colorectal Screening: Application of Multiple Mediation Methods

Abstract: Background: Colorectal cancer screening participation is lower among recent immigrants than among Canadianborn individuals. We assessed whether this screening disparity is mediated by access to regular primary care physicians (PCP).Methods: Pooling years 2003 to 2014 of the Canadian Community Health Survey, lifetime screening in respondents aged 50 to 75 years of age who immigrated in the previous 10 years (n ¼ 1,067) was compared with Canadian-born respondents (N ¼ 102,366). Regression-and inverse probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…37 Studies suggested that those with higher educations are able to better realize and communicate their health care needs, and realize the benefits of continuous PHC. 38 This results in a more effective use of the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…37 Studies suggested that those with higher educations are able to better realize and communicate their health care needs, and realize the benefits of continuous PHC. 38 This results in a more effective use of the health care system.…”
Section: Discussionmentioning
confidence: 99%